Customer Service Management at Bank BTN KCP Condong Catur: Review of SOPs and Service Procedures - Imbang Yuniannita; Yunita Fitri Wahyuningtyas (Universitas Nusantara PGRI Kediri, 2024)
Facing the complexity of the banking industry, especially in the era of globalization and digitalization, Bank Tabungan Negara (BTN) needs to anticipate the changes that occur. This study uses several methods in data collection, in this study are interviews, observations and documentation, but emphasizes more on the interview method to dig up information and obtain good and complete information. The qualitative data processing and analysis stage is carried out based on interview data, observations and documentation. Data analysis at this stage consists of data reduction and presentation followed by drawing conclusions. Service management based on SOP (Standard Operating Procedure) at BTN KCP Condong Catur bank, with a service management system in accordance with standard operating procedures and management functions has been realized and is running well. The service procedure at BTN KCP Condong Catur Bank has been carried out well, one example of the service procedure process is by controlling the services at BTN KCP Condong Catur by holding annual controls from BTN KCP Condong Catur.